A case study on the comparison between conventional and Islamic (Takaful) insurance / Nor Hazlin Hussin - Hussin, Nor Hazlin (Faculty of Business and Management, 2009)
In Malaysia the operation of Takaful is licensed and regulated by the Takaful Act 1984. The Act was specially promulgated and passed by the Malaysian Parliament with a view of ensuring that Takaful as a sector within the Islamic financial system would grow in an orderly manner. The insurance industry in Malaysia is licensed and regulated by a separate act. At present, the supervisory authority vested under the Takaful Act is the Central Bank of Malaysia (Bank Negara Malaysia) whereby the Governor of the Bank is also the Director General of Takaful. Islamic finance has developed mainly in two directions namely Islamic banking and Islamic insurance (Takaful). All human beings are invariably exposed to the possibility of meeting catastrophes and disasters giving rise to misfortunes and sufferings such as death, loss of limbs, accident, and destruction of business or wealth. Notwithstanding the belief of all Muslims in Qadha-o-Qadr, Islam provides that one must find ways and means to avoid such catastrophes and disasters wherever possible, and to minimizeh is or his family's financial losses should such events occur. One possible way out is to buy an insurance cover as in the conventional system. Different views have been expressed about the status of conventional insurance from the point of view of Islam. Takaful is not a new concept in Islamic commercial law. The contemporary jurists acknowledge that the foundation of shared responsibility or Takaful was laid down in the system of ‘Aaqilah’, which was an arrangement of mutual help or indemnification customary in some tribes at the time of the Holy Prophet. The contract of Takaful provides solidarity in respect of any tragedy in human life and loss to the business or property. The policyholders pay subscription to assist and indemnify each other and share the profits earned from business conducted by the company with the subscribed funds. The distinction between the conventional insurance and Takaful business is more visible with respect to investment of funds. While insurance companies invest their funds in interest-based avenues and without any regard for the concept of Halal-o-Haram,